985Sex differences in the incidence of renal cell carcinoma: results from the EPIC cohort study. (2nd September 2021) - Muller, David; Scelo, Ghislaine; Riboli, Elio
Abstract: Background: Incidence of renal cell carcinoma (RCC) is two-fold higher in men compared with women. This ratio has been remarkably stable, both geographically and over time. We investigated whether established risk factors for RCC can explain the higher incidence in men. Methods: 230, 399 participants in the EPIC cohort study with complete data for BMI, history of hypertension, and smoking variables were included. Cox regression models with age as the time-scale were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for sex. Results: We identified 690 incident RCC cases. The marginal HR [95% CI] for men versus women was 2.30 [1.98, 2.69]. There was no strong evidence for interactions between hypertension, BMI, or smoking status and sex. Adjusting for BMI, hypertension and smoking variables did not materially affect the estimate (HR: 2.18 [1.85, 2.56]), accounting for only 10% of the observed excess risk. In contrast, smoking factors alone could account for 88% of the observed excess risk of lung cancer for men (marginal HR: 2.19 [2.02, 2.38]; adjusted HR: 1.14 [1.04, 1.25]) Conclusions: The two-fold higher incidence of RCC in men compared with women cannot be explained by established risk factors. Key messages: Whilst obesity, hypertension, and smoking are established risk factors for RCC, they cannot account for the greater incidence among men compared with women. This indicates the presence of as yet unknown factors to which men are more susceptible than women.